Kebijakan Pendidikan Islam Sebagai Kebijakan Publik - Umi Rahmawati; Qolbi Khoiri (Departement of Mathematics Education, 2023)
Abstract The concept of Islamic Religious School was widely used in Indonesian education even before Indonesia gained independence. Since Indonesia acquired independence, Islamic Education has not yet achieved a standing in the idea of national education that is similar to that of general Education. As soon as Law No. 20 of 2003, which governs the National Education System, was established, Islamic Religious Education in Indonesia began to take shape. The following are the study's limitations: 1) What was the motivation behind Law No. 20 of the National Education System's 2003 passage? 2) How successful is the law no. 20 of 2003 on the national education system's policy on Islamic religious education? What impact will this have on Indonesia's attempts to advance Islamic religious education? Key words: Implications, National Education System Law No. 20 of 2003, Islamic Religious Education, Policy.